(untitled) (ARTEKS : Jurnal Teknik Arsitektur, 2026)
The rising temperature of the Kayutangan Heritage Corridor (KHC) poses a risk to the sustainability of its historical value and the comfort of its microclimate. The UHI phenomenon in KHC development is vulnerable to the decline of historical value and microclimate quality. This study aims to assess the potential of the Brantas River Watershed as a buffer zone for KHC development. The method used is a three-stage analysis: first, land surface temperature (SST) data analysis to identify the distribution of hot and cold spots; second, direct surface temperature measurements to validate the LST; and third, Computational Fluid Dynamics (CFD) simulation of the existing thermal conditions of the KHC and its buffer zone. The LST distribution pattern forms the basis for formulating a UHI mitigation model. The CFD simulation results indicate that the Brantas River Watershed, which borders the KHC, has the potential to serve as a buffer zone for Kayutangan development. This mitigation strategy enables Kayutangan development to transform into a more resilient area through integration with its buffer zone.